1993
DOI: 10.3354/meps093001
|View full text |Cite
|
Sign up to set email alerts
|

Indications of density-dependent effects from comparisons of sperm whale populations

Abstract: Standardized studies of living sperm whales Physeter macrocephalus were carried out in 3 areas with very different recent whaling intensities. These were off the Galapagos Islands, where there seems to have been little recent whaling, off the Seychelles and Amirantes Islands, where animals were regularly caught by passing Soviet whalers, and off mainland Ecuador, adjacent to the area whaled very heavily from Paita, Peru. Sperm whale densities off the Galapagos were about 4. 2 times higher than off the Seychell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Length measurement distributions (from 7.7 to 17.8 m) from photographs of sperm whales off the Galápagos from 1985 to 1987 (834 measurements; Waters and Whitehead 1990) and off Ecuador during 1991 (343 measurements; Kahn et al 1993) were compared with 2641 acoustic length measurements of coda producers from the same areas during the same periods (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Length measurement distributions (from 7.7 to 17.8 m) from photographs of sperm whales off the Galápagos from 1985 to 1987 (834 measurements; Waters and Whitehead 1990) and off Ecuador during 1991 (343 measurements; Kahn et al 1993) were compared with 2641 acoustic length measurements of coda producers from the same areas during the same periods (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…We then compared the length distributions of coda producers in groups off the Galápagos from 1985 to 1987 and off Ecuador during 1991 with photographic measurements of whales from the same groups during these studies Kahn et al 1993). The photographic measurement technique is that of Gordon (1990) and requires photographs being taken perpendicular to the whales that show its back and the horizon.…”
Section: Ipi Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that females appeared to be smaller (by some 0.8 m) at every age when compared with other sperm whale populations (Ohsumi 1971, Gambell 1972. A nearly identical size distribution (8-11 m) was found for 79 females and immature sperm whales measured photogrammetrically off the Seychelles in 1990 (Kahn et al 1993).…”
Section: Discussionmentioning
confidence: 85%
“…KAHN et al (1993) mention that during the last 40 years of sperm whaling the preference for catching mature males ended up changing the adult sex ratio in some areas (CLARKE et al 1980). It has been suggested that this change resulted in a disruption of the sperm whale's mating system, leading to a reduction in pregnancy rates, thus lessening the potential of the population for recovery (CLARKE et al 1980, MAY & BEDDINGTON 1980, WHITEHEAD 1987.…”
Section: Discussionmentioning
confidence: 99%